Modern technology of modeling of organizational preparation of territories of construction objects - Chernyshev, D.; Tugay А.; Malykhin, M. (Ways to Improve Construction Efficiency, 2019)
The article examines the most important of which is the need to review traditional perceptions of organizational building technology and the need to use a comprehensive approach to address the challenges of preparing sites for a single cluster. Two approaches have been applied to the estimation of the solution of problems in the cycles of organizational preparation: regular (this is the issuance of tasks (goals, tasks) by the manager of the construction project, indicating the means, possible restrictions, indicative methods and time for their implementation) and program-targeted (this is the issuance of the construction project manager tasks (goals, tasks), indicating the means, methods and time for their implementation). It is revealed that geoinformation modeling involves the collection and processing of the following data: information on the spatial and attribute description of individual parts of the cluster, regulatory background data on the capacities of individual industries and resource requirements, as well as additional information on the design characteristics of underground communications. It is envisaged to systematize this data and to integrate it into a single information model. The main tasks and sequence of stages of implementation of complex organizational training were also revealed. Analysis of automation of construction processes allowed to highlight the key points of improvement and problematic issues of information support for the development of territories, the main of which are the shortcomings of the classification and coding systems of information; its duplication in the preparation of construction sites. It is suggested to use 4D modeling to organize the preparation of construction sites. Based on project information coming from the 4D model, the system automatically generates purchase requests; conducts a tender for the supply of equipment, materials and components; identifies the supplier (from the replenished database of suppliers); determines the terms of shipment and delivery of equipment, materials and components to the construction site. All this information, including the status of purchases of equipment, components and materials, is visualized in the information model. Thus, the given tools of geoinformation modeling will allow to use them in cycles of complex organizational preparation.